2012
DOI: 10.1007/s10948-012-1560-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Deposition of YBa2Cu3O7 Superconducting Film on MgO Templates Spray Pyrolyzed on Hastelloy C276

Abstract: Pulsed laser deposition (PLD) was used to deposit YBCO on MgO-buffered C276 substrates in order to evaluate the quality of the deposited MgO films which were deposited by spray pyrolysis. The characterization of the thin films was done using scanning electron microscopy, atomic force microscopy, electron backscattered diffraction, X-ray diffraction 2θ -scans, rocking curve (ω-scans), phi scan, pole-figure measurements, and AC susceptibility. It was found that c-axis oriented YBCO films were grown on c-axis ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The AC susceptibility measurements (Fig. 11) showed that YBCO gave broad superconducting transition temperatures with a T C onset of 83.6 K. This is close to what was found by others [19] and to that which was found by us on Hastelloy C276 [23]. This proves that the cheaper 321 steel is a good choice as a substrate for thin film deposition and could be used as an alternative for the expensive C276.…”
Section: Spray Pyrolysis Of Mgo From Acetate Precursorssupporting
confidence: 86%
See 2 more Smart Citations
“…The AC susceptibility measurements (Fig. 11) showed that YBCO gave broad superconducting transition temperatures with a T C onset of 83.6 K. This is close to what was found by others [19] and to that which was found by us on Hastelloy C276 [23]. This proves that the cheaper 321 steel is a good choice as a substrate for thin film deposition and could be used as an alternative for the expensive C276.…”
Section: Spray Pyrolysis Of Mgo From Acetate Precursorssupporting
confidence: 86%
“…In our previous work [22] it was found that high concentrations of magnesium nitrate were needed to detect the MgO peak. Besides that, the superconducting properties of the deposited YBCO films were lower compared to those when the acetate precursor was used [23]. Because of that, no further investigation will be carried out on magnesium nitrate precursor and the acetate precursor is to be investigated.…”
Section: Spray Pyrolysis Of Mgo From Nitrate Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-0239). Sample-A shows the stronger intensity of characteristic peaks than others, which is previously reported that the intensity of the X-ray diffraction (XRD) peaks increases with increasing precursor concentration, temperature and thickness [12][13][14][15]. Electronic supplementary material, figure S1a shows the XRD patterns of Sample-A-precursor and Sample-O-precursor.…”
Section: Resultsmentioning
confidence: 69%
“…However, AISI 3xx SS can be subjected to localized pitting corrosion. Pitting corrosion can be caused by exposure to aggressive chloride anions [41]; it is initiated when chloride anions are introduced into the working environment and reach a critical value, forming a thin layer of chloride ion-rich electrolyte on the stainless steel surface [42]. However, the adsorption of an inhibitor on a steel surface and the formation of a protective film could reduce or inhibit the pitting corrosion, as mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%